A Decadal Climatology of Chemical, Physical, and Optical Properties of Ambient Smoke in the Western and Southeastern United States. Issue 1 (4th January 2020) - Bian, Qijing; Ford, Bonne; Pierce, Jeffrey R.; Kreidenweis, Sonia M.
Abstract: Biomass burning is a major source of summertime fine particulate matter in the United States, degrading air quality and affecting human health and climate. Fuels, burn conditions, and fire types vary across the United States, which may impact smoke composition and optical properties. We use the Hazard Mapping System to track smoke plumes for 10 years from 2008 to 2017, focusing on three U.S. regions: Southeast, Pacific West, and Southwest. Combining this geospatial data set with AErosol RObotic NETwork (AERONET) columnar data, and Interagency Monitoring of Protected Visual Environments (IMPROVE) network in situ observations, we define "smoke‐influenced days" and derive the properties of smoke aerosol for April through September, encompassing the main fire seasons across the United States. We find in the IMPROVE surface measurement that the elemental carbon fraction of smoke in the Southeast is statistically different from and lower than that in the west, consistent with more‐smoldering prescribed fires in the southeast. We find in the AERONET columnar observations that the mean single scattering albedo of smoke (at 675 nm) is lower in the two western regions (~0.94) compared to the southeast (~0.96), consistent with the differences in composition and fire types, which implies that the compositional differences at the surface may be representative of the column. Higher relative humidity in the southeast and less dust associated with smoke also appear to contribute to the higher smoke single scattering albedo relative to the west. Our results show that smoke properties vary regionally, with implications for models, data assimilation, and remote‐sensing. Key Points: We derive long‐term mean smoke chemical and optical properties across three regions of the United States Smoke in the southeastern United States has higher sulfate content and single scattering albedo than smoke in the western United States Burn conditions, relative humidity, and dust coemitted with smoke may drive the variability in smoke properties between regions